Strengthening Gender Equality in Small Business and Achieving Sustainable Development Goals (SDGS): Comparative Analysis of Kenya and Nigeria - Timilehin Olasoji Olubiyi; Bolaji Jubril; Oluwaseun Samson Sojinu; Rosemary Ngari (Program Studi Administrasi Negara Universitas Serang Raya, 2022)
There is an increasing understanding that Sustainable Development Goals (SDGs) can protect the planet, reduce inequality and tackle poverty. However, many small business owners and entrepreneurs in Africa still see it as a misery. This study aims to determine whether the SDG's goal number five (5) is being used to motivate gender equality among small and medium-sized enterprises in Africa, particularly in Kenya and Nigeria. The study focuses on female entrepreneurs. The target population comprised 110 randomly selected businesses operating in Embakasi East constituency in the Embakasi ward in Nairobi County, Kenya, and Ikeja Local Government in Lagos Mainland of Lagos state Nigeria. The sample size was determined by relying on a prior study on women in business in Africa. The study adopted a qualitative research method, administering open-ended interviews to the respondents, and the response rate was 90.91%. Descriptive statistical analysis was adopted, and the examination of the data demonstrated that a significant number of women working in SMEs are unaware of the SDGs in the two countries despite the United Nations (UN) supporting gender equality. The research concludes that there is still a considerable difference between men and women in SMEs in Africa and the awareness of SDG goals is limited. It is recommended that the management of small businesses, regulators, and policymakers should increase the knowledge of the global goals for more awareness and sustainability adoption in African countries. This can also support sustainable business growth and close the inequality gap in small African businesses